Biocomposites from (Anadara granosa) Shells Waste for Bone Material Applications - Siti Hajar, Saharudin; Jun Haslinda, Haji Shariffuddin; Noor Ida Amalina, Ahamad Nordin (IOP Publishing, 2017)
The overall objective for this study is to determine the effect of biopolymer types and ratio on producing biocomposites derived from cockle (Anadara granosa) shells waste. In this study, two types of biopolymer were used i.e. sodium alginate and carboxymethyl cellulose. These biocomposites are meant for bone material applications. The processes involved in producing the biocomposites were pre-treatment of the cockle shells, formation of CaCO3 in aragonite form and finally the synthesis of biocomposites. All samples have undergone physicochemical and mechanical analyses to determine their crystallinity, purity, functional group, surface morphology, elemental compounds and compressive strength using X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM), Electron Dispersive X-ray Analysis (EDX) and Universal testing machine (UTM). The CaCO3-biocomposites have been prepared using different ratio of biopolymer and different types of biopolymers. The physicochemical properties of the biocomposites are not affected by the ratio and types of biopolymers. Yet, the ratio and types of biopolymers have influenced the mechanical properties of biocomposites. The biocomposite with lesser amount of biopolymer has denser structure and greater mechanical strength. Comparison between types of polymers revealed that biocomposite with carboxymethyl cellulose has greater mechanical strength compared to biocomposite with sodium alginate.